Use of youth-friendly health services and predictive factors: A community-based analytical cross-sectional study among young people in the Tamale metropolis. - Vivian Awuah; Gifty Apiung Aninanya; Benson Bionkum Konlan (PLoS ONE)
Globally, teenage pregnancies, unsafe abortions and sexually transmitted infections are on the increase among young people. However, their knowledge and uptake of youth-friendly sexual and reproductive health services are low. This study evaluated young people's knowledge, attitude and utilization of youth-friendly health services in the Tamale Metropolis. 420 young people aged between 15 and 24 years were proportionately selected from four suburbs within the Tamale metropolis and a Likert scale was used to collect quantitative data. To determine the correlation between the relevant characteristics and attitudes toward youth-friendly health services, a logit model and chi-square statistics were applied. Respondents' knowledge of youth-friendly health services was low (69%). A majority (71%) of them had a negative attitude towards youth-friendly health services and 63% of them had never used such services before. Level of education and religion were significantly associated with the knowledge levels of respondents while religion, employment status and individuals contributing to decision-making concerning the health of the participants were associated with attitudes towards the services. Cost and level of education were also associated with the uptake of youth-friendly health services. In conclusion, most young people had low knowledge, poor attitudes and low uptake of youth-friendly health services. Predictors of uptake of youth-friendly services were cost and educational level. The study suggests the need for Ghana Health Service to rigorously embark on sensitization programmes on the benefits of utilising youth-friendly health services and the cost of patronising these services could be subsidized to promote its utilization among the youth.